2015
DOI: 10.1016/j.jmbbm.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Critical buckling pressure in mouse carotid arteries with altered elastic fibers

Abstract: Arteries can buckle axially under applied critical buckling pressure due to a mechanical instability. Buckling can cause arterial tortuosity leading to flow irregularities and stroke. Genetic mutations in elastic fiber proteins are associated with arterial tortuosity in humans and mice, and may be the result of alterations in critical buckling pressure. Hence, the objective of this study is to investigate how genetic defects in elastic fibers affect buckling pressure. We use mouse models of human disease with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(68 citation statements)
references
References 36 publications
4
64
0
Order By: Relevance
“…While limitations exist, the use of the two-layered model with dispersed collagen fiber provides an approach better link arterial mechanical stability to specific structural changes in the media and/or adventitia layers as well as to microstructural changes under pathological conditions due to aging, atherosclerosis and arterial degenerative diseases. Furthermore, our previous work has demonstrated elastin degradation in arteries reduces the critical buckling pressure (Lee et al, 2012; Luetkemeyer et al, 2015). Combined, these studies demonstrated arterial mechanical stability is linked to the extracellular matrix of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…While limitations exist, the use of the two-layered model with dispersed collagen fiber provides an approach better link arterial mechanical stability to specific structural changes in the media and/or adventitia layers as well as to microstructural changes under pathological conditions due to aging, atherosclerosis and arterial degenerative diseases. Furthermore, our previous work has demonstrated elastin degradation in arteries reduces the critical buckling pressure (Lee et al, 2012; Luetkemeyer et al, 2015). Combined, these studies demonstrated arterial mechanical stability is linked to the extracellular matrix of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Q 66 = G 12 (16) According to Betty-Maxwell theorem the Young's modulus and Poisson's ratios should fulfil the following equation…”
Section: Laminated Composite Materialsmentioning
confidence: 99%
“…Also the phenomena, model analyses, experimental measurements, effect on blood flow, and clinical relevance have been discussed. From this and further works Han et al clearly showed that mechanical buckling of aorta artery is an important issue for vasculature, in addition to wall stiffness and strength, and requires further studies [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…All are relevant to the critical buckling load [4], and elastic response of the arteries. In this report, we attempt to investigate the effects of internal inflation pressure on column buckling load, axial and circumferential.…”
Section: Introductionmentioning
confidence: 99%